Correction: Diiridium(iii) complexes: luminescent probes and sensors for G-quadruplex DNA and endoplasmic reticulum imaging. (8th May 2017) - Anjong, Tikum Florence; Kim, Gyoungmi; Jang, Ha Yoon; Yoon, Juyoung; Kim, Jinheung
Abstract : Correction for 'Diiridium(iii ) complexes: luminescent probes and sensors for G-quadruplex DNA and endoplasmic reticulum imaging' by Tikum Florence Anjong et al., New J. Chem., 2017, 41, 377–386.